Policies facilitating firm adjustment to globalization - Hoekman, Bernard M. 1959- (Policy research working paper, 2004)
"Hoekman and Javorcik focus on policies facilitating firm adjustment to globalization. They briefly review the effects of trade and investment liberalization on firms, focusing on within-industry effects. They postulate that governments' role in supporting the process is to (1) ensure that firms face "right" incentives to adjust, and (2) intervene in areas where market failures are present. Their main message is that while many policies could be adopted to address market failures, they need to be carefully designed and implemented in a stable macroeconomic environment. An institutional infrastructure that supports the functioning of modern markets is most important. Proactive support policies of whatever stripe should be subject to cost-benefit analysis, based on the existence of an identified market failure, and monitored for performance and cost effectiveness. Transparency and accountability are critical in ensuring that interventions accomplish their intended objectives rather than being vehicles for rent seeking. This paper--a product of the Trade Team, Development Research Group--is part of a larger effort in the group to examine the effects of globalization on developing countries"--World Bank web site